Mental Health, Addictions and Suicides - A Likely Partnership? - Konkin, Patrick (University of British Columbia, 2000)
The article considers a probable relationship existing between mental health issues, addictions and suicide within the context of marginalization experienced by Canada's First Nations people. No Mental Health Evaluation and Community Consultation Unit - Lifenotes - UBC